Constituents of flowers essential oils of Smirnovia iranica Sabeti from Iran - mansureh ghavam (Advanced Herbal Medicine, 2017)
Background and aims: Smirnova iranica Sabeti is one of the valuable and adapted shrub native species to the sandy fields of Central Iran and of Fabaceae family that in terms of the production of forage and soil conservation and creating a beautiful landscape and medicinal value is critically important. No study has been conducted on this plant essence in Iran, so far.Methods: In the habitat of the plant, located in Kashan sandy areas, during flowering in the third week of April in each site, flowers were collected and after extraction of essential oils using simultaneous method of distillation and extraction using organic solvents, a chromatography device connected to a mass spectrometer (GC/MS) was used in order to identify the combinations of essential oils.Results: The essence yields were 0.02% and the color of essential oils was yellowish. The important and main combinations of essential oils were Hexadecanoic acid, Tetradecanoic acid and 6,10,14-Trimethyl-2-pentadecanone  which consisted more than 10 percent of the composition.Conclusion: It can be concluded that Smirnova iranica sabeti is a versatile plant found in sandy fields of Iran with medicinal, anti-virus, anti-cancer and anti-bacterial properties.